HYGIENIC ANALYSIS OF THE NUTRITIONAL STATUS OF UZKIMYOSANOAT WORKERS - Ortikov Bobomurod Baymamatovich; Buriboyev Eldar Mamurjonovich; Khaydarov Shovkatjon Madaminjon ogli; Saidova Gulbakhor Tursunaliyevna (The Bioscan, 2025)
Objectives: To analyze the dietary status of workers in a manufacturing enterprise both at home and in the workplace. To conduct a comparative analysis of the daily food consumption levels of workers in the winter-spring and summer-autumn seasons against physiological normative indicators. Based on the obtained results, to recommend a preventive dietary plan. Aims: To conduct a hygienic analysis of the absolute dietary status of workers at AMMOFOS MAKSAM-Uzkimyosanoat. Methods: The study included 283 workers (185 men and 98 women) employed at AMMOFOS MAKSAM-Uzkimyosanoat between 2021 and 2023. Data on their actual dietary intake at home and in the workplace was collected and analyzed using a questionnaire survey. Results: The consumption levels of 38 types of food products in the daily diet of Uzkimyosanoat enterprise workers were analyzed for the winter-spring and summer-autumn seasons. The consumption of flour products ranged from 64.3–82.8% in winter-spring and 35.0–42.8% in summer-autumn. Bread consumption followed a similar trend, with 47.4–71.9% in winter-spring and 39.8–47.6% in summer-autumn. The consumption of pasta was 17.7–15.6 g and 12.6–10.8 g, confectionery products 30.6–27.9 g and 6.8–8.1 g, sugar 1.61–2.47 times and 1.57–2.43 times, margarine 302–376% and 244–234%, and salt 4.8–4.1 g and 2.7–1.8 g, all of which were found to be consumed in excess. Meanwhile, the supply indicator for milk and dairy products was only 56.3–55.1% in winter-spring and 29.3–31.3% in summer-autumn. Conclusion: The daily intake levels of the above-mentioned food products were found to exceed physiological norms, whereas the intake of essential nutrients was insufficient. These dietary imbalances can lead to disruptions in rational and healthy nutrition, ultimately affecting workers’ health. Ensuring proper nutrition is crucial for maintaining and strengthening workers’ health and enhancing their work productivity.